Tooling role in activating the work of the private sector in Iraq - Mohammed, Asmaa Jasim (Opción, 2020)
Iraq is one of the countries demanding today to work to reduce dependence on oil rents and the trend towards economic diversification. Hence the importance of the study in the search for Islamic contracts, which comes in the forefront of tooling and its role in activating the economic movement and private sector development of small and medium enterprises. The study reached a number of conclusions, including the importance of holding tooling, because it is used in several sectors, as well as its importance for small entrepreneurs; as the entry of Islamic banks as financier of these projects.